2022
DOI: 10.3390/foods11111611
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Drying Methods on the Volatile Components of Ginger (Zingiber officinale Roscoe) by HS-GC-MS Coupled with Fast GC E-Nose

Abstract: Ginger (Zingiber officinale Roscoe) is one of the most popular spices in the world, with its unique odor. Due to its health benefits, ginger is also widely used as a dietary supplement and herbal medicine. In this study, the main flavor components of gingers processed by different drying methods including hot air drying, vacuum drying, sun-drying, and vacuum-freeze drying, were identified on the basis of headspace-gas chromatography coupled with mass spectrometry (HS-GC-MS) and fast gas chromatography electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…3 B). Recently, many studies reported that gingerols, shogaols, terpenes are the main constituents in ginger, which are also considered as the material basis of its flavor ( Yu et al, 2022 , Zhang et al, 2021 ). These components consist of C—H, O—H and N—H groups with strong multiplicative and synchrotron absorption in the NIR regions (7000 cm −1 –4000 cm −1 ) ( Nagy et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 B). Recently, many studies reported that gingerols, shogaols, terpenes are the main constituents in ginger, which are also considered as the material basis of its flavor ( Yu et al, 2022 , Zhang et al, 2021 ). These components consist of C—H, O—H and N—H groups with strong multiplicative and synchrotron absorption in the NIR regions (7000 cm −1 –4000 cm −1 ) ( Nagy et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ginger ( Zingiber officinale Roscoe) is a spicy condiment and is often eaten in fresh form or made into dried slices and powder for flavoring ( Yu et al, 2022 ). Due to its unique flavor, high nutrition, and medicinal value, ginger is extensively consumed as a flavoring agent, dietary supplement, herbal medicine, and the raw materials of many desserts and beverages, such as ginger tea, ginger candies and ginger beer ( Srinivasan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instrument analysis methods include gas chromatography–mass spectrometry (GC–MS), gas chromatography–olfactometry (GC–O), liquid chromatography–mass spectrometry (LC–MS), gas chromatography–ion mobility spectrometry (GC–IMS), and so on [ 34 , 35 , 36 , 37 ]. GC–MS has become a common method for the detection of volatile compounds in food flavor due to its advantages of high sensitivity, low detection limit, and accurate qualitative analysis [ 38 , 39 , 40 ]. GC–IMS is a rapid detection technique for volatile organic compounds that combines the advantages of the high separation performance of gas chromatography with the fast response and high sensitivity of the ion migration spectrum [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that dried could promote the formation of volatile compounds. The content of volatile components of VFDS in SD-BFDP samples was the lowest, probably because volatile compounds such as aldehydes, esters, heterocycles, acids, and other volatile compounds in frozen samples are more likely to be lost by sublimation under vacuum conditions [ 24 ].…”
Section: Resultsmentioning
confidence: 99%